The Liberal Party, Free Trade and the 1841 Election1. (13th June 2019) - Rowe, Christopher
Abstract: It is a paradox that the Liberal Party's electoral defeat in 1841 attested to its underlying strength and vitality. This article focuses on the impact on party unity of the free trade measures advocated by the ministry in the months preceding its fall. The Liberal Party's bold electoral platform antagonised its protectionist MPs, a group previously overlooked in the historiography, but fell short of the demands of its radical wing for political reform. While all the ingredients for fragmentation existed, unity prevailed. Protestations of loyalty to the leadership could be heard from the mouths of Liberal MPs of all shades, from stalwart protectionists who coalesced around the ministry on traditional foreign policy grounds through to the most fervent radicals who celebrated its 'new' direction. Such findings of cohesion contradict accounts which have hitherto viewed the 1841 electoral defeat as evidence of the party's inchoateness. Indeed, this article shifts the historiographical narrative away from addressing why the Liberals lost to the more pertinent issue of why the losses suffered were not greater. In answering that question, both the sensitivity with which the financial agenda was presented by ministers and the flexibility of different sections of the Liberal Party in interpreting and presenting the free trade measures to the electorate are underlined. Above all, Lord John Russell is rehabilitated as a 'popular' leader and his importance in the development of the nascent Liberal Party is unearthed.